Reference group, personality dan social class: perannya terhadap keputusan belanja produk skincare: Studi pada konsumen gen Z di TikTok shop - Putri, Kartika Anggraeni Sudiono; Linggasari, Filda Septa (Nur Science Institute, 2024)
This research aims to analyze the role of reference groups, social class, and personality in determining shopping decisions for skincare products at the TikTok Shop. Gen Z dominates most consumers of skin care products and TikTok users in Indonesia. The study employs a qualitative approach with data collection conducted through a survey in Malang City. The sample is 180 respondents, conducted through purposive sampling with a few criteria, namely Gen Z, as active TikTok users who have purchased at TikTok Shop. Data analysis used multiple linear regression. The results show that partially or simultaneously, the three independent variables, namely reference group, social class, and personality, influence the decision to shop for skincare products at TikTok Shop. Therefore, the decision to shop for skincare products in Gen Z was influenced by the preferences they received from the reference group and then adjusted based on each individual's personal needs and purchasing power.